Influence of biochar, mycorrhizal inoculation, and fertilizer rate on growth and flowering of Pelargonium (Pelargonium zonale L.) plants - Conversa, Giulia; Bonasia, Anna; Lazzizera, Corrado; Elia, Antonio (Frontiers in Plant Science, 2015)
Peat is the most common substrate used in nurseries despite being a very expensive and a non-renewable material. Peat replacement with biochar could be a sound environmental practice, as it is produced from waste biomass, but evaluation of biochar as a potting substrate is needed. Ratios of peat:biochar of 100:0, 70:30, 30:70 (BC0, BC30, and BC70, respectively), two fertilizer rates (FERT1, FERT2) and arbuscular mycorrhizal fungi (AMF) inoculation were tested on potted pelargonium plants. Plant growth, flowering, bio-physiological and nutritional responses, and root mycorrhization were evaluated. The BC30 mixture did not affect plant growth compared with pure peat. However, BC30 in combination with FERT2 treatment was more effective in enhancing nitrogen (N) and chlorophyll leaf concentrations, and leaf and flower numbers. The BC70 mixture depressed plant growth, flowering traits and root mycorrhization. Leaf N concentration was below the sufficiency range reported for pelargonium growth. Leaf concentration of phosphorous (P) was adequate in pure peat and in BC30 but it dropped close to sub-optimal values in BC70. The pH value of the mixtures lowered P availability, though in BC30 the mycorrhizal activity could have allowed adequate P plant uptake. In BC70 plants, the deficiency of both N and P might be a reason for the observed growth reduction. The inoculation of the substrate with selected AMF improved plant growth (higher dry biomass, greater floral clusters, larger and more abundant leaves) and quality resulting in unstressed (lower electrolyte leakage and higher relative water content values) and greener leaves (low L* and C*, high chlorophyll content) and in more intensely colored flowers. We conclude that biochar can be applied in nursery/potted plant production provided that the proportion in the peat mixture does not exceed 30%. Furthermore, AMF inoculation contributed to achieving the best plant performance in 30% biochar amended medium.